Adaptasi Laporan Keuangan Pada Entitas Nonlaba Berdasarkan Isak 35 (Studi Kasus pada Universitas Ibrahimy Sukorejo Situbondo) - Imro'atun Shoimah; Siti Maria Wardayati; Yosefa Sayekti (ITB AAS INDONESIA, 2021)
This research aims to analyze and adapt the financial reporting of non-profit entities based on Interpretation of Financial Accounting Standards 35 (ISAK 35): concerning the Presentation of Financial Statements for Non-Profit Oriented Entities. Namely the interpretation of the Statement of Financial Accounting Standards 1 (PSAK 1): concerning the Presentation of Financial Statements. For other accounting provisions for non-profit entities, it refers to the Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) and Sharia Accounting Standards (SAS). Qualitative research was conducted with a case study at the University of Ibrahimy Sukorejo Situbondo. The results of this study, it is necessary to change the accrual basis recording method with the double entry system, preparation of adjusting journals to then compilation of financial position reports, comprehensive income reports, changes in net assets reports, cash flow reports and notes on financial reports based on ISAK 35. Adaptation of university financial reports Ibrahimy based on ISAK 35 is carried out by adjusting the required account posts by Ibrahimy University with the accounts stated in the Interpretation of Financial Accounting Standards 35 (ISAK 35)